Inhibition of human mevalonate kinase by allosteric inhibitors of farnesyl pyrophosphate synthase - Salari, Saman; Lee, Hiu‐Fung; Tsantrizos, Youla S.; Park, Jaeok (FEBS open bio, 2024)
Mevalonate kinase is a key regulator of the mevalonate pathway, subject to feedback inhibition by the downstream metabolite farnesyl pyrophosphate. In this study, we validated the hypothesis that monophosphonate compounds mimicking farnesyl pyrophosphate can inhibit mevalonate kinase. Exploring compounds originally synthesized as allosteric inhibitors of farnesyl pyrophosphate synthase, we discovered mevalonate kinase inhibitors with nanomolar activity. Kinetic characterization of the two most potent inhibitors demonstrated Ki values of 3.1 and 22 nm. Structural comparison suggested features of these inhibitors likely responsible for their potency. Our findings introduce the first class of nanomolar inhibitors of human mevalonate kinase, opening avenues for future research. These compounds might prove useful as molecular tools to study mevalonate pathway regulation and evaluate mevalonate kinase as a potential therapeutic target. Mevalonate kinase constitutes a key regulatory step in the mevalonate pathway, an established drug target for its role in the synthesis of isoprenoid molecules. Using a structure‐based rational approach, we identified several synthetic compounds that inhibit mevalonate kinase with nanomolar potency. Further analysis revealed their mode of inhibition and the structural features that correlate with their inhibitory potency.